Pengembangan Sistem Steganografi Berbasis Web Menggunakan Metode Least Significant Bit (LSB) - Aiman Fawwaz; Alifmulya Rahman; Muhammad Akbar; Rahmad Hidayah Damanik (JIKUM: Jurnal Ilmu Komputer, 2026)
Concealing digital information within images has become increasingly important with the growing demand for data security in the digital era. This research develops a web-based steganography system using the Least Significant Bit (LSB) method to hide secret messages within digital images. The system is designed with a user-friendly web interface featuring two main functions: (1) "Hide Message" feature to embed secret messages into images and (2) "Extract Message" feature to extract hidden messages from stego-images. The implementation includes optional security features with password protection, enabling users to perform encoding and decoding processes without requiring specialized technical expertise. Modern web technologies are utilized to ensure accessibility, fast processing speed, and preservation of image quality after message embedding. System testing includes functionality evaluation, image quality analysis using Peak Signal-to-Noise Ratio (PSNR) and Mean Squared Error (MSE) metrics, and user experience testing. Research results demonstrate that the system successfully extracts messages with perfect accuracy ("yok kerja yok") while maintaining image visual quality. The system can be applied in secret communication applications, digital watermarking, and intellectual property protection. In conclusion, the development of this web-based steganography system provides a practical and accessible solution to protect digital information privacy through a user-friendly interface suitable for all user levels.